Strategi Pengembangan Atribut Green City Kota Malang - Septina Dwi Rahmawati; Khoiriyah Trianti; Radiatul Husni (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2024)
A green city is a city with good planning that has an environmentally friendly character and seeks to manage its resources for everything that focuses on environmental balance. In an effort to create a green city, various planning and implementation programs have been and are being carried out, both by the government, private sector and also the community in order to realize the concept of a green city. One form of sustainable program to support, this is known as the Green City Development Program (Program Pengembangan Kota Hijau) or more easily abbreviated as P2KH which refers to the Regional Spatial Planning Plan (Rencana Tata Ruang Wilayah) or abbreviated as RTRW. Green cities themselves have indicators called eight (8) green city attributes, including: green open space, green waste, green transportation, green water, green energy, green building, green community, and green planning and design. The background on this research is presented in three criteria, including empirical problems, theoretical frameworks, and legal foundations used as references or legal guidelines for implementing the green city concept. It is known that the complexity of society's demands increases as the population increases. This of course becomes a challenge in managing environmental resources. Problems such as traffic jams, air pollution, increasing volumes of waste, slums, flooding and other social inequality problems, which of course with the increasing population, logically result in the living area becoming increasingly narrow. What happened in Malang City is no exception. Malang City has great potential for better services, especially in the context of realizing a green city. The research results show that there are eight green city attributes that have been implemented in several activities in Malang City. In practice, these eight attributes need continuous development. The concept of a green city is not a simple concept that can be planned once and then realized, it is a holistic, continuous and sustainable concept. Therefore, this research provides an in-depth look at strategies for developing green city attributes in Malang City using a qualitative approach. The strategy for developing green city attributes in the city of Malang is carried out through the SOAR and SWOT analysis stage, the development stage, the role enhancement stage, the support and development stage of appropriate technology, coordination and synergy between actors, as well as evaluation and supervision in improving the quality of the green environment and public awareness of development of the green city concept in Malang City.